Delay and deservingness after winning the lottery - Andrew J. Oswald; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2008)
Economics rests upon a set of presumptions about how human beings are affected by income. Yet causal evidence is scant. This paper reports a longitudinal study of randomly selected lottery winners. Remarkably, we show that it takes almost three years before they enjoy their money. We develop a model of dissonance and deservingness. We argue that, despite the tradition of economics, human beings may weight differently the different kinds of income that accrue to them. If so, it is not sufficient to describe utility by a function u(y), and it is not true that 'a dollar is a dollar'.
Keywords: I31; J3; 330; well-being; lottery income; deservingness; cognitive dissonance; happiness; Glücksspiel; Emotion; Zufriedenheit; Haushaltseinkommen; Test